Implementation of the Number Head Together Learning Method in Increasing Student Activeness - Nisa', khoirun; Wahyudi, Wahyudi; Chabibi, Moch Faizz ‘Ilmi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The aim is to determine the Number Head Together learning method in increasing student’s activity in classroom learning. This research is qualitative research. Data collection uses observation, interview, and documentation techniques. Data were analyzed using triangulation techniques. The research results show that the Number Head Together learning method succeeded in changing the learning atmosphere in the classroom which was previously monotonous to become more interesting. In its implementation, there are advantages and disadvantages, but with this method, students become active and enthusiastic in learning. So it can be concluded that the Number Head Together learning method is very appropriate to apply in schools so that learning is more effective and prevents students from getting bored while studying.